Gene loss, repression, amplification, and horizontal acquisition shape galactose/melibiose metabolism in fission yeast - Xiao-Min Du; Fang Suo; Li-Lin Du (Proceedings of the National Academy of Sciences, 2026)
Natural variation in metabolism is a key driver of microbial adaptation. While galactose utilization is well studied in budding yeasts, it remains poorly understood in the fission yeast Schizosaccharomyces pombe . Here, we reveal extensive natural variation in galactose utilization across S. pombe isolates—from complete deficiency (Gal − ) to exceptionally fast growth (Gal F ). Gal − strains fall into two classes: one with deletions of the gal gene cluster (via three distinct mechanisms) and another with intact but repressed gal genes. In contrast, Gal F is driven by an amplified gene cluster absent from the reference genome—the gal – mel cluster (GMC)—which also confers melibiose utilization (Mel + ). Mel + is exclusively linked to the GMC, except in one strain harboring a standalone melibiase gene. Phylogenetic analyses indicate that horizontal gene transfer may underlie these adaptive traits. Together, our work demonstrates how diverse mechanisms—gene loss, repression, amplification, and horizontal acquisition—shape metabolic diversity and ecological specialization in fission yeast.